PERAN ORANG TUA DALAM MENDUKUNG MOTIVASI BELAJAR ANAK DI SEKOLAH DASAR - Putri Maulidyana Takbir; Syamsu A Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Parental support plays an important role in determining the success of a child’s education. Both the attention and encouragement provided by parents are crucial factors in the student learning process. This study aims to analyze the influence of parental support on the learning motivation of elementary school students. The research employed a qualitative method with a descriptive approach, involving parents and fourth-grade students as subjects. Data were collected through interviews and observations, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that all parents provide support for their children's learning motivation, which includes emotional support, appreciation, practical assistance, and information. However, instrumental support—such as accompanying children during study time and providing learning needs—has not been carried out optimally. Many parents still rely on learning facilities provided by the school, and economic limitations cause some learning needs to remain unmet. Informational support, such as guidance when children experience learning difficulties, is also not optimal because some parents do not fully understand the learning materials and are occupied with work. In fact, parents are the first and foremost educators in developing a child’s potential. Therefore, more optimal efforts are required so that children's learning motivation can develop well. Keywords: parental role, learning motivation, elementary school, child learning